2011
DOI: 10.1007/s10340-011-0373-2
|View full text |Cite
|
Sign up to set email alerts
|

Voracity of Coccinella undecimpunctata: effects of insecticides when foraging in a prey/plant system

Abstract: Coccinella undecimpunctata L. is a euryphagous predator established in Azores that offers interesting potential as a control agent in the context of integrated pest management (IPM). However, to further develop IPM against aphids, it is important to evaluate the effects that insecticides might have on voracity. Thus, we proposed to evaluate the effects of pirimicarb and pymetrozine on the voracity of 4th instar larvae and adults of C. undecimpunctata, under distinct scenarios of exposure to chemicals within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…Sublethal effects of insecticides could affect population dynamics (Stark and Banks 2003) through impairment to behavioral and physiological traits (Kerns and Stewart 2000;Desneux et al 2006a;Arnó and Gabarra 2011;Cabral et al 2011;Shahout et al 2011;Stara et al 2011;Han et al 2012). Studies have demonstrated that exposure to lethal or sublethal doses/concentrations of pesticides could reduce insect longevity and fecundity (Desneux et al 2006b;Zeng et al 2006;Wang et al 2008;Bao et al 2009;Biondi et al 2012;Zappalà et al 2012) and disturb key behavioral traits (Desneux et al 2004a, b;Ramirez-Romero et al 2008;Cordeiro et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Sublethal effects of insecticides could affect population dynamics (Stark and Banks 2003) through impairment to behavioral and physiological traits (Kerns and Stewart 2000;Desneux et al 2006a;Arnó and Gabarra 2011;Cabral et al 2011;Shahout et al 2011;Stara et al 2011;Han et al 2012). Studies have demonstrated that exposure to lethal or sublethal doses/concentrations of pesticides could reduce insect longevity and fecundity (Desneux et al 2006b;Zeng et al 2006;Wang et al 2008;Bao et al 2009;Biondi et al 2012;Zappalà et al 2012) and disturb key behavioral traits (Desneux et al 2004a, b;Ramirez-Romero et al 2008;Cordeiro et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Acute toxicity (lethal effect) and selectivity of pesticides has been examined in predators (Zhu et al 1998;Qiu et al 2000), including in predatory coccinellid beetles (Hao et al 1990;Zhu et al 1998;Wu et al 2007;Urbaneja et al 2008;Xi 2008;Cabral et al 2011). However, in addition to their lethal effect, pesticides also can induce various sublethal effects.…”
Section: Introductionmentioning
confidence: 96%
“…We studied the lethal toxicity of imidacloprid to S. japonicum through various exposure routes that aimed at representing various exposure scenarios (and because exposure methods could have an impact on results, Stark et al 1995;Desneux et al 2006a). We also studied the effects of imidacloprid on functional response of S. japonicum to B. tabaci eggs and on predator voracity as sublethal effects on these key predator traits (O'Neil 1997;Cabral et al 2011;Madadi et al 2011) could greatly reduce predator impact on B. tabaci. This study constitutes the basis for future guidelines for imidacloprid rational use, and it can help optimizing IPM programs involving use of both natural enemies and imidacloprid against B. tabaci in China.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, pymetrozine appears to act by preventing plant-sucking insects from inserting their stylus into the plant tissue (Ausborn et al 2005). Pymetrozine was classified as slightly harmful to the common green lacewing Chrysoperla carnea Stephens (Neuroptera: Chrysopidae) (Rezaei et al 2007) and the predatory bug Orius insidiosus (Hemiptera: Anthocoridae) (Moscardini et al 2013), and had no adverse effects on the predators Coccinella undecimpunctata (Coleoptera: Coccinellidae) (Cabral et al 2008(Cabral et al , 2011.…”
Section: Discussionmentioning
confidence: 98%